2022
DOI: 10.6007/ijarbss/v12-i8/14642
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Communication Strategies and Fear of Oral Presentation among Undergraduates

Abstract: Communication strategies are basically ways utilised by students to manage their interactions in a target language learnt. Fear of oral presentations is still common among students due to many reasons. In order to cope with such fear when communicating in English, communication strategies (CS) are employed by students to assist them in communicating in the most effective way they feel they could. This preliminary study on CS and fear of oral presentations are conducted to investigate how CS influences oral pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There have been many past studies on the fear of oral presentation. The study by Ahmad et al (2022) was conducted to investigate issues on how factors leading to fear of oral presentations among undergraduates influence their oral presentations. The data was collected from 51 students from three clusters: Science and Technology, Social Science and Humanities, and Business and Management.…”
Section: Past Studies On Fear Of Oral Presentationmentioning
confidence: 99%
“…There have been many past studies on the fear of oral presentation. The study by Ahmad et al (2022) was conducted to investigate issues on how factors leading to fear of oral presentations among undergraduates influence their oral presentations. The data was collected from 51 students from three clusters: Science and Technology, Social Science and Humanities, and Business and Management.…”
Section: Past Studies On Fear Of Oral Presentationmentioning
confidence: 99%
“…The fear of communicating in English is still common among the non-native speakers of English due to many reasons. A study conducted by Ahmad et al (2022) among 51 undergraduate students in a public university found that most of the students were inclined to use more strategies in influencing their oral presentation. This may be caused not only by the lack of basic English grammar and vocabulary but also by deficiency in the use of appropriate Communication Strategies (CSs) for many communicative contexts.…”
Section: Literature Review Features Of Communication Strategiesmentioning
confidence: 99%